Synthesis of α-Fe2O3 and α-Fe2O3/SiO2 Composite from Geothermal Waste by Sol-Gel Method and Their Characterization - Mulmeyda, Rinda; Reinardo Ramawijaya Widakusuma; Sabrina Putri Chaerani; Agus Purwanto; Rifqi Almusawi Rafsanjani; Habib Muhammad Zapar; Bagaskoro Pranata Ardhi (Chemistry and Materials, 2025)
Iron oxide materials, especially hematite (α-Fe2O3), have many important applications. Improving the characteristics and physical properties of hematite has been widely developed, one of which is to combine it as a composite structure with porous materials such as silica (SiO2) as α-Fe2O3/SiO2 composite. This research aims to synthesize α-Fe2O3 particles and α-Fe2O3/SiO2 composites. The α-Fe2O3/SiO2 composite was successfully synthesized by using geothermal waste as an alternative source of silica prepared by the sol-gel method. Both synthesized samples were characterized by X-ray diffraction, scanning electron microscopy equipped with energy dispersive spectroscopy, and X-ray fluorescence techniques. The results showed that silica composites on hematite structure slightly affect the morphology, color, or particle size compared to α-Fe2O3.